Pengenalan Bahasa Inggris dalam Pembelajaran PAUD di Taman Kanak-Kanak Kota Bandung - Ernawulan Syaodih; Mubiar Agustin; F Febriyanti (Universitas Pendidikan Indonesia (UPI), 2022)
Introducing English from an early age is a positive and absolute thing to improve the quality of Indonesian human resources, especially in facing the current era of globalization. This study aims to provide a factual and accurate picture of learning at Darul Hikam Kindergarten in introducing English to early childhood, which includes planning, implementation and evaluation processes. The method used to support this research is descriptive analytic. The subjects of this study were group B students of Daul Hikam Kindergarten. The research data were obtained through interview guides, observation guidelines, documentation studies and literature studies. It can be concluded that English for early childhood at Darul Hikam Kindergarten has been introduced through methods that can support the learning process so that it can run well and be fun, and can be an advantage of Darul Hikam Kindergarten schools.